The Ethical Leadership, Role’s in Building Organizations Culture in Primary Educational Institutions in Dammam Region (The International Journal for Scientific Research, 2024)
The study aimed to reveal the role of ethical leadership in building organizational culture in educational institutions in the Dammam region. To achieve the goal of the study, the descriptive analytical approach was followed, so that a stratified random sample of school leaders was selected, numbering (13) leaders, (37) educational and administrative supervisors, and (3) Department director, (41) department heads, and (79) other leadership professions. The electronic questionnaire was applied to them, and the study concluded the following:1. There is a high degree of practicing ethical leadership among them, as well as a large degree of practicing organizational culture in primary educational institutions in the Dammam region.2. There was also a close, statistically significant correlation at the level of (0.01) between ethical leadership and its role in the organizational culture of the educational institutions in the study sample.3. Most of the leaders in the study strongly agreed on the degree of practicing ethical leadership with regard to the dimensions of human, personal, and professional relations behaviors.4. Most of the leaders in the study agreed to a moderate degree on the degree of organizational culture with regard to its elements, which are values, beliefs, norms, and finally, expectations.
Keywords: Ethical Leadership; Organizational Culture; Educational Institutions